Information and communication technologies in the processes of logistics services provided: economic essence, features, and development prospects in the context of digital transformation (Economics and region, 2023)
The given paper examines modern information and communication technologies in the context of digitalization of the Ukrainian economy, which play a truly key role in this issue. At the same time, digital solutions are becoming important, allowing maximum consideration of the requirements of the external environment (globalization, digitalization, internationalization). The COVID-19 pandemic has been a test for logistics enterprises and a catalyst for the introduction of digital solutions not only to solve current problems, but also to adapt to new realities. It has been determined by authors that at this stage, enterprises engaged in the development of their information systems and the implementation of modern digital solutions receive a number of competitive advantages. The paper pays special attention to the case of “Nova Poshta”, a leading logistics enterprise that is actively developing logistics processes and introducing digital solutions in order to maintain a leading position in the market. It has been established what benefits a logistics enterprise will receive from improving information and communication technologies, namely: reducing the risk of errors, improving the quality of personalized services and the level of customer satisfaction, improving last-mile delivery, ensuring security and a guaranteed reduction in fraud. It has been studied that digitalization processes implemented through information and communication technologies provide competitive advantages, even if they are expensive, and contribute to intensive data processing, minimizing time losses, increasing labor productivity, reducing errors and the risk of losses. It has been also established that currently there are a number of factors that can significantly hinder the development of logistics enterprises. These are as follows: imperfect legislation, insufficient investment, low quality infrastructure, insufficient number of terminals, logistics centers, insufficient quantity and quality of vehicles, etc.
Keywords: logistics; logistics processes; digital solutions; information and communication technologies; communication